Teacher Strategies for Developing Environmental Care Attitudes in Early Childhood: A Literature Review - Tari; Henny; La Jeti (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to analyze teachers' strategies in developing environmental care attitudes among early childhood children through a literature review approach. The study reviewed 19 nationally accredited SINTA journal articles published between 2021 and 2026. The data were collected through a documentation study by identifying relevant articles using the keywords early childhood teachers' strategies, early childhood environmental education, and environmental care attitudes through Google Scholar. Data were analyzed using content analysis, which consisted of data reduction, data display, and conclusion drawing. The findings indicate that the most dominant learning approaches were ecopedagogy and the contextual approach, each identified in eight articles, while two articles employed a learning-through-play approach and one article integrated both the contextual and ecopedagogy approaches. The most frequently applied instructional methods were the project method and habituation, whereas the dominant instructional techniques consisted of hands-on practice and observation. Environment-based classroom management was also found to effectively support the development of environmental care attitudes among young children. The findings further reveal that learning strategies based on direct experiences are more effective in fostering environmental care attitudes than learning that relies solely on instructional approaches.